A Three-Dimensional Spatial Metaphorical Representation of Generation Implied in Han Kin Terms - Li, Huijuan; Zhang, Jijia; Zhang, Entao (Frontiers in Psychology, 2021)
Abstract concepts can be represented in the brain by means of metaphors. Generation refers to the seniority in the family or clan, implies the implementation of different attitudes required by kinship, and contains profound psychological, emotional, and social factors. Generation as an abstract concept is related to abstract concepts such as power, social status, importance, and time. The Conceptual Metaphor Theory based on the embodied theory proposes that abstract concepts are represented by actual sensorimotor experiences. Generation implied in Han kin terms is often represented by multiple spatial terms. According to Conceptual Metaphor Theory, the current study predicted that generation could be represented by multiple spatial metaphors. We designed six experiments to investigate this issue. The results showed that (1) the up–down and left–right positions in which kinship words were presented affected the processing of the concept of generation; (2) the processing of kinship words also affected up–down and left–right spatial information perception; and (3) the processing of the concept of generation could also automatically activate the front–back spatial operation and induce the embodied simulation of body movement. In sum, the results suggested that generation might be represented by the three-dimensional spatial metaphor of vertical, horizontal, and sagittal axes, which are influenced by the sensorimotor system.